Floral folk art in cross stitch - Jones, Durene (Tuva Publishing, 2021)
"A range of designs that are suitable for all sewing abilities. The essence of this book is to keep it simple, fun, and easy to stitch. With that in mind most of the designs are sewn using only whole cross stitch, and back stitch is kept to a minimum. The patterns vary in sizes. From small quick stitch designs for tags, pincushions, key fobs, and cards, to larger, more involved designs for notebook covers, pictures, fire screens, or table cloths. Many of the designs can easily be used in multiple ways. A single small design or band could be used to edge a place mat, table cloth, towel, or curtain tie back, or you could combine several designs together to make a sampler. A stunning collection of patterns for both new and experienced stitchers alike."--Amazon.com.